Factors influencing tax e-filing and role of trust of electronic filing system - Raja Haslinda Bint Raja Mohd Ali, Murtala Zakari, Saliza Binti Abdul-Aziz, (Opción, 2019)
Trust has received much attention in IS literature in the area of e-commerce in view of its significance influence on uncertainties and risks associated with e-shopping and other e-commerce transactions. In comparison to huge trust literature in IS and e-commerce landscape, there is little attention on the influence of trust of system in the context of electronic tax system. The aim of this paper is to extend UTAUT Model by incorporating perceived trust of system as a proposed research model for electronic tax filing adoption.